Final analysis of the randomized trial on imatinib as an adjuvant in localized gastrointestinal stromal tumors (GIST) from the EORTC Soft Tissue and Bone Sarcoma Group (STBSG), the Australasian Gastro-Intestinal Trials Group (AGITG), UNICANCER, French Sarcoma Group (FSG), Italian Sarcoma Group (ISG), and Spanish Group for Research on Sarcomas (GEIS) - Casali, Paolo G.; Le Cesne, A.; Velasco, A. P.; Kotasek, D.; Rutkowski, P.; Hohenberger, Peter; Fumagalli, E.; Judson, I. R.; Italiano, A.; Gelderblom, H.; Penel, N.; Hartmann, J. T.; et al. (Annals of oncology, 2021)
Background - In 2004, we started an intergroup randomized trial of adjuvant imatinib versus no further therapy after R0-R1 surgery in localized, high/intermediate-risk gastrointestinal stromal tumors (GIST) patients. Interim analysis results were published in 2015 upon recommendation from an independent data review committee. We report the final outcome of the study. - Patients and methods - This was a randomized, open-label, multicenter phase III trial carried out at 112 hospitals in 12 countries. Patients were randomized to 2 years of imatinib, 400 mg daily, or no further therapy after surgery. The primary endpoint was imatinib failure-free survival (IFFS), while relapse-free survival (RFS), relapse-free interval (RFI), overall survival (OS) and toxicity were secondary endpoints. Adjusting for the interim analyses, results on IFFS were assessed on a 4.3% significance level; for the other endpoints, 5% was used. - Results - Nine hundred and eight patients were randomized between January 2005 and October 2008: 454 to imatinib and 454 to observation; 835 patients were eligible. With a median follow-up of 9.1 years, 5 (10)-year IFFS was 87% (75%) in the imatinib arm versus 83% (74%) in the control arm [hazard ratio (HR) = 0.87, 95.7% confidence interval (CI) (0.65; 1.15), P = 0.31]; RFS was 70% versus 63% at 5 years and 63% versus 61% at 10 years, [HR = 0.71, 95% CI (0.57; 0.89), P = 0.002]; OS was 93% versus 92% at 5 years and 80% versus 78% at 10 years [HR = 0.88, 95% CI (0.65; 1.21), P = 0.43]. Among 526 patients with high-risk GIST by local pathology, 10-year IFFS and RFS were 69% versus 61%, and 48% versus 43%, respectively. - Conclusions - With 9.1 years of follow-up, a trend toward better long-term IFFS in imatinib-treated patients was observed in the high-risk subgroup. Although the difference was not statistically significant and the surrogacy value of such an endpoint is not validated, this may be seen as supporting the results reported by the Scandinavian/German trial, showing a sustained small but significant long-term OS benefit in high-risk GIST patients treated with 3 years of adjuvant imatinib.